The Role of Spondyloarthrosis in the Structure of Pain After Hip Arthroplasty - Gayko, G.V.; Haluzynskyi, O.A.; Sulyma, O.M.; Pidhaietskyi, V.M. (TERRA ORTHOPAEDICA, 2020)
Summary. In the structure of complications, pain syndrome, which is not associated with infection or instability of the components of the endoprosthesis, remains a serious problem due to the difficulties of diagnosis and treatment. The cause of the residual pain may be the presence of spondyloarthrosis of the lumbar spine in the patient. Objective: to determine the role of spondyloarthrosis of the lumbar spine in the structure of pain after hip arthroplasty. Materials and Methods. A sample and retrospective analysis of the case histories of 138 patients with hip-lumbar syndrome who underwent hip arthroplasty in the Department of Traumatology and Orthopedics of Adults of the SI “Institute of Traumatology and Orthopedics of NAMS of Ukraine” was carried out. All patients were examined clinically and radiographically. Additionally, all patients were examined by a neurologist with the determination of the neurological status and diagnosis. Evaluation of the effectiveness of hip arthroplasty in order to improve the clinical and functional characteristics of the link hip joint – spine was carried out according to the Haris and Oswestry functional scales. Results. The analysis of the database of patients in them proved that the lumbar vertebrae at the L2-L4 level are more often affected. In hyperlordosis, degenerative lesions occur in the posterior column of the lumbar spine in the form of spondyloarthrosis, which is clinically manifested by lumbodynia; with hypolordosis, the anterior column suffers more, which is clinically manifested by the presence of lumboishalgia. Total arthroplasty of patients with hip-lumbar syndrome contributes to statistically significant (p≤0.05) reduction in pain syndrome and improvement of function both in the hip joint and the lower back. Residual, less intense, pain syndrome after arthroplasty was most intensive in patients with hypolordosis (24.11 points according to Oswestry’s classification). Сonclusions. The studies carried out to determine the role of spondyloarthrosis of the lumbar spine in the structure of pain after hip arthroplasty will contribute to the further development of a clinical diagnostic and therapeutic algorithm for patients with hip-lumbar syndrome.